Neurophysiological outcomes of combined transcranial and peripheral electromagnetic stimulation on DOMS among young athletes: A randomized controlled trial - Hugo Kériven; Alberto Sánchez-Sierra; Ángel González-de-la-Flor; María García-Arrabé; María Bravo-Aguilar; Marta de-la-Plaza-San-Frutos; Guillermo García-Pérez-de-Sevilla; José Francisco Tornero Aguilera; Vicente Javier Clemente-Suárez; Diego Domínguez-Balmaseda (PLoS ONE, 2025)
This study investigates the potential benefits of a combined electromagnetic stimulation therapy, involving both transcranial and peripheral stimulation (paired-associative electromagnetic stimulation), to address Delayed Onset Muscle Soreness (DOMS). Forty-eight young athletes participated in this randomized controlled trial and were allocated to the control group (n = 12), the peripheral group (n = 13), the transcranial group (n = 11), and the combined group (n = 12). Surface electromyography (EMG) during leg extension and peak force were used to assess the response of the peripheral nerves. Additionally, force dynamometry and the Counter Movement Jump (CMJ) test were employed to evaluate the progression of lower limb sports performance over the study period. All assessments were performed before and after the eccentric exercise session that induced DOMS, as well as at 24-, 48-, and 72-hours post-exercise. The combined group exhibited significantly greater muscle activation in both electromyographic recordings compared to the other groups (p < 0.001), with large effect sizes for EMG peak in vastus medialis (η²p = 0.786), vastus lateralis (η²p = 0.821), and rectus femoris (η²p = 0.816). Moreover, the combined group demonstrated a marked improvement in both force dynamometry (η²p = 0.593) and CMJ performance (η²p = 0.520), with significant differences observed compared to the other groups (p < 0.001). In conclusion, paired-associative electromagnetic stimulation shows promise in enhancing muscle activity and improving lower limb performance by facilitating recovery from DOMS in young athletes. The study was registered with the Australian New Zealand Clinical Trials Registry (ACTRN12623000677606) on June 23 rd , 2024 ( https://anzctr.org.au/ ).